Usage of Twitter by state-owned enterprises to communicate with customers: A case of Transnet South Africa - Mello, Tsebiso Lisbeth (School of Management Studies, 2021)
Social media is proving to be a critical factor for firms moving towards digital marketing strategies. Substantial economic advantage is gained when companies make use of social media platforms such as Twitter to modernise their businesses and start interactive communication with their target market. Social media can have a great impact on the efficiency and performance of state-owned enterprises, which are often plagued by information irregularities that compromise information disclosure and lower the standards of accountability within the state-owned enterprises. Without social media, customers are often unable to evaluate the product and services that the state-owned enterprise is offering before making an offer. An interpretivist research paradigm was adopted and informed this study which applied a mono qualitative research methodology. Sample elements were selected using non-probability purposive and convenience sampling techniques. Data was gathered through a pre-designed interview guide with open-ended questions from the research site. In addition, the case study research design was used in this study. All interview transcriptions were recorded with the aid of a voice recorder and exported to NVivo 11 for cleaning and coding, resulting in emerging themes. Thematic data analysis was performed on the data sets, allowing a detailed discussion of each theme in line with research objectives. The study established that adopting and using social media was the appropriate strategy for firms. Firms, especially state-owned enterprises, reached a larger audience. In addition, the study established that the quality of content uploaded and shared on social media should be of very high quality to project a positive image of the organisation. Appointing dedicated senior personnel to manage the social media strategy enhanced the effectiveness of social media. The study recommended that further research be conducted on other types of social media to allow organisations a wider selection of choices. The study indicated that employees were compelled to use Twitter; thus, a policy shift in the use of social media required managers to put in place Information Communications Technology and Privacy and Security Policies. In order to educate everyone in the organisation, management had to ensure that its policies did not infringe on human rights.